(untitled) (Quest Journal of Management and Social Sciences, 2026)
Background: In recent years, mergers and acquisitions (M&A) have become a strategic approach adopted by banks and financial institutions worldwide to enhance competitiveness, increase operational efficiency, and strengthen financial stability. In Nepal, regulatory reforms and policies introduced by the Nepal Rastra Bank have encouraged consolidation among banks and financial institutions to create stronger and more sustainable financial entities. Understanding how these structural changes influence customer satisfaction is therefore important for ensuring the success of post-merger operations. Purpose: This study aims to examine the impact of mergers and acquisitions (M&A) on customer satisfaction in Nepalese banks and financial institutions (BFIs), identifying key challenges and potential managerial solutions for improving service quality post-M&A. Design/methodology /approach: A descriptive and explanatory research design was adopted. Data were collected from 405 bank customers in Kathmandu Valley using convenience sampling and a structured questionnaire. The data were analyzed using Microsoft Excel for descriptive statistics and SmartPLS 4.0 for inferential analysis, including Structural Equation Modeling (SEM) to assess relationships between service quality dimensions and customer satisfaction. Findings: The majority of respondents are male and maintain banking relationships primarily as depositors. Almost half of the respondents experienced challenges due to M&A, including changes in product and service offerings (31.45%), integration issues in bank systems (29.3%), and lack of effective communication (21.51%). Among the five SERVQUAL dimensions, tangibility (β = -0.235, p = 0), reliability (β = 0.235, p = 0), and assurance (β = 0.336, p = 0) significantly influence customer satisfaction, while responsiveness and empathy were not significant. Proposed solutions include offering new and improved products and services, enhancing communication, and ensuring reliable system integration to address post-merger challenges. Conclusion: The study emphasizes the importance of improving service quality after M&A in Nepalese BFIs. By focusing on enhanced products, effective communication, reliable systems, and upgraded service delivery, banks can increase customer satisfaction and ensure successful post-merger operations. Keywords: Merger and Acquisition, Customer Satisfaction, Banking Sector, Nepalese Financial Institutions, Service Quality